Left bundle branch area pacing is superior to right ventricular septum pacing concerning depolarization‐repolarization reserve. (10th December 2019) - Wang, Jingfeng; Liang, Yixiu; Wang, Wei; Chen, Xueying; Bai, Jin; Chen, Haiyan; Su, Yangang; Chen, Ruizhen; Ge, Junbo
Abstract: Introduction: Left bundle branch area pacing (LBBAP) has recently been reported to be a new physiological pacing strategy with clinical feasibility and safety. The present study aims to investigate depolarization‐repolarization measures including QT interval, QT dispersion (QTD), and Tpeak‐end interval (Tp Te ) in this novel LBBAP strategy. Methods and Results: A total of 131 pacing‐indicated patients were prospectively enrolled and randomized to the LBBAP group (n = 66) and right ventricular septum pacing (RVSP) group (n = 65). LBBAP was successfully achieved in 61 subjects with stable lead performance and comparable complications (ie, pocket hematoma, lead perforation, and dislodgement) compared with RVSP. Of the 61 patients with successful LBBAP, the mean LV peak activation time was 67.89 ± 6.80 ms, with the LBB potential mapped in 46 cases (75.4%). Electrocardiogram (ECG) indices were compared between these two groups before and after implantation. As a result, LBBAP yielded a narrower paced QRS duration (121.49 ± 9.87 ms vs 145.62 ± 8.89 ms; P < .001), shorter QT interval (434.16 ± 32.70 ms vs 462.66 ± 32.04 ms; P < .001), and QTc interval (472.44 ± 33.30 ms vs 499.65 ± 31.35 ms; P < .001), lower QTD (40.10 ± 8.68 ms vs 46.11 ± 10.85 ms; P = .001), and QTc D (43.57 ± 8.78 ms vs 49.86 ± 11.98 ms; P = .001), and shorter Tp Te (96.59 ± 10.76 ms vs 103.77 ± 10.16 ms; P < .001) than RVSP. However, Tp Te /QT ratio did not differ between these two groups (0.223 ± 0.026 vs 0.225 ± 0.022; P = .733). Furthermore, LBBAP displayed less increased QRS duration, QTc interval, QTD, QTc D, and a more shortened QT interval compared with RVSP (all P < .05). Conclusion: LBBAP proves to be a feasible and safe pacing procedure with better depolarization‐repolarization reserve, which may predict lower risk of ventricular arrhythmia and sudden cardiac death.